Islamic Law and Customary Law in the Prohibition of Sogit Marriage in Sabah, Malaysia - Alhusni; Mohmad Jeofrey, Siti Adibah Binti; M. Zaki (Islamic Law and Social Issues in Society, 2025)
This study examines the interaction between Islamic law and customary law in the context of sogit marriage prohibitions among the Muslim Kadazandusun community in Ranau, Sabah, Malaysia, focusing on applying ʿurf within a framework of legal pluralism. Employing a socio-legal approach combined with empirical methods—including legal document analysis, in-depth interviews with customary and religious authorities, and direct observation—this research identifies eleven categories of marriages within the Adat Resam (AR) of Himbaan Village, analyzed through the Islamic legal concept of ʿurf (custom). The findings reveal a pattern of selective accommodation: AR 8 (polygamy) and AR 10 (marriage preceding that of an elder sibling) are classified as ʿurf ṣaḥīḥ (valid custom), whereas AR 1 (cousin marriage) and AR 11 (marriage with a relative of a former spouse) constitute ʿurf fāsid (invalid custom). Other prohibitions involving illicit sexual relations and familial disruption (AR 2–7) are excluded from ʿurf categorization, as they are explicitly prohibited in Islam. The sogit system, originally an animistic conflict-resolution mechanism involving blood sacrifice or monetary compensation, has evolved into a practice of social reconciliation aligned with the Islamic concept of iṣlāḥ. The Native Customary Law Enactment 1995 institutionalizes this negotiation process. This study contributes significantly to contemporary Islamic legal scholarship in Southeast Asia by demonstrating the flexible application of uṣūl al-fiqh principles, particularly ʿurf, in the pluralistic legal realities of a Muslim minority society. The model of selective integration illustrates how customary and Islamic legal systems may operate complementarily, provided they do not contradict sharīʿa, thereby enabling the preservation of cultural identity alongside religious obligations.